Please help solve the below functional equation for a function $f: \mathbb R \rightarrow \mathbb R$: \begin{align} &f(-x) = -f(x) , \text{ and } f(x+1) = f(x) + 1, \text{ and } f\left(\frac 1x\right) = \frac{f(x)}{x^2} \\ &\text{ for all } x \in \mathbb R \text{ and } x \ne 0 . \end{align}

I know this will be solved by cyclic substitutions, but I'm unable to figure out the exact working. Can someone explain step wise?

  • $\begingroup$ The functional equation forces $f(q)=q$ for all $q\in\Bbb{Q}$. Is $f$ supposed to be continuous, perhaps? $\endgroup$ – Servaes Oct 29 '18 at 10:52
  • $\begingroup$ If $f$ is continuous, then it is true. But I don't think it's true otherwise. $\endgroup$ – TonyK Jul 3 at 10:21
  • $\begingroup$ It seems I was wrong $-$ continuity is not required. See @Michael Rozenberg's answer. $\endgroup$ – TonyK Jul 3 at 10:27

I don't know if this is what is meant with "cyclic substitutions", but it is a solution.

First, we observe that $$ f(0)=0, f(1)=1, f(-1)=-1 $$ has to be true. Also, it suffices to determine $f(x)$ for $x>0$, because the rest follows from the condition $f(-x)=-f(x)$.

Let $x>0$. Applying some of the conditions, we have $$ \begin{aligned} f(x)+1 &= f(x+1) \\ &= f(1(x+1)^{-1})(x+1)^2 \\ &= f(1-x(x+1)^{-1})(x+1)^2\\ &= (1+f(-x(x+1)^{-1}))(x+1)^2\\ &= (1-f(-x(x+1)^{-1}))(x+1)^2\\ &= (1-f(-x(x+1)^{-1}))(x+1)^2\\ &= (1-f((x+1)x^{-1})x^2(x+1)^{-2})(x+1)^2\\ &= (1-f(1+x^{-1})x^2(x+1)^{-2})(x+1)^2\\ &= (1-(1+f(x^{-1}))x^2(x+1)^{-2})(x+1)^2\\ &= (1-(1+f(x)x^{-2})x^2(x+1)^{-2})(x+1)^2\\ &= (x+1)^2-x^2-f(x)\\ \end{aligned} $$

This yields $f(x)=x$.


For $x\neq0$ and $x\neq1$ we obtain: $$f(x)=x^2f\left(\frac{1}{x}\right)=x^2f\left(\frac{1}{x}-1+1\right)=x^2\left(f\left(\frac{1}{x}-1\right)+1\right)=$$ $$=x^2+x^2f\left(\frac{1-x}{x}\right)=x^2+x^2\cdot\frac{f\left(\frac{x}{1-x}\right)}{\frac{x^2}{(x-1)^2}}=x^2+(x-1)^2f\left(\frac{x}{1-x}\right)=$$ $$=x^2+(x-1)^2f\left(\frac{1}{1-x}-1\right)=x^2+(x-1)^2\left(f\left(\frac{1}{1-x}\right)-1\right)=$$ $$=x^2-(x-1)^2+(x-1)^2\cdot\frac{f(1-x)}{(1-x)^2}=2x-1-f(x-1).$$ Thus, $$f(x)+f(x-1)=2x-1$$ or $$f(x)+f(x+1)=2x+1,$$ which gives $$f(x)+f(x)+1=2x+1$$ or $$f(x)=x.$$ Now, show that $f(0)=0$ and $f(1)=1.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.